2012
DOI: 10.1902/jop.2011.110099
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Early Orthodontic Force on Periodontal Healing After Autotransplantation of Permanent Incisors in Beagle Dogs

Abstract: The results of this study demonstrate that orthodontic force promotes periodontal ligament healing and that early force loading may prevent dentoalveolar ankylosis; however, a period of rest of ≥2 weeks is recommended for the autotransplants before loading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 23 publications
0
17
0
4
Order By: Relevance
“…The results of the present study are in accordance with previous studies in which immediate and controlled function after avulsion and replantation did not have a detrimental effect on the healing potential . Yang et al observed significantly more resorption and less healing when loads were applied in the first week after autotransplantation .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of the present study are in accordance with previous studies in which immediate and controlled function after avulsion and replantation did not have a detrimental effect on the healing potential . Yang et al observed significantly more resorption and less healing when loads were applied in the first week after autotransplantation .…”
Section: Discussionmentioning
confidence: 99%
“…Nayak et al found that orthodontic tooth movement in rats promoted initiation of cell differentiation at or around the perivascular areas of blood vessels in the periodontium and concluded that tooth movement stimulates the production of signalling that leads to cellular proliferation in the alveolar marrow. Yang et al evaluated the application of orthodontic forces on the periodontal healing of autotransplanted teeth in dogs and reported these forces resulted in lower ankylosis and promotion of periodontal ligament re‐attachment and proliferation. Evidence‐based science from the orthopaedic literature, in which immediate and controlled function of injured tissues were applied, has demonstrated better rehabilitation and less physical impairments .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Orthodontic forces may affect root development and pulp vitality when applied to teeth with immature apices; therefore, it is recommended that tooth movement be started between 6 and 9 months after autotransplantation once pulp and periodontal healing has been achieved and root development is complete (17,18). However, a recent study performed on dog's teeth has proven that light, continuous orthodontic forces of 50 g applied 2 weeks after the autotransplantation procedure may prevent ankylosis and improve healing of the PDL (19).…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al (5) reported a correlation between the amount of load and the amount of movement in an orthodontic force experiment on autotransplanted front teeth in dogs. Because tooth movement and root resorption are related (6), there is great interest in how much tooth movement is possible without root resorption.…”
Section: Introductionmentioning
confidence: 99%